The Causes of Afghanistan's backwardness and its emergence in the light of tradition - Jalali, Sayed Mohammad (Journal of Social Sciences - Kabul University, 2022)
Every Islamic country should try to take the lead from other countries in religious and religious affairs, especially our dear country (Afghanistan), which has faced and is facing problems at different times. Most backward countries are under the influence of other countries. Case: ( وَأَعِدُّواْ لَهُم مَا اسْتَطَعْتُمَ مُن قُوَّةٍ3). It is clear from the holy verse that Muslims are ahead of others in every way, not following in the footsteps. Today, Muslims have lagged behind others in worldly affairs. I went to insert it in the light of tradition and finally conclude Racial and political differences have provoked them to fight against each other. And also the political differences on this earth continue that one group thinks they are right and the other side is wrong while they are both Muslims. In any case, the advantages and positive points of one group may be more obvious than the other, but the purpose of this superiority is not cursing and cursing over others.